2017
DOI: 10.1371/journal.pone.0169420
|View full text |Cite
|
Sign up to set email alerts
|

Association of TLR3 L412F Polymorphism with Cytomegalovirus Infection in Children

Abstract: Intracellular Toll-like receptor 3 (TLR3) recognizes viral double-stranded RNA (dsRNA) and activates antiviral immune responses through the production of type I interferons (IFNs) and inflammatory cytokines. This receptor binds to dsRNA molecules produced during human cytomegalovirus (HCMV) replication. TLR7 senses viral single-stranded RNA (ssRNA) in endosomes, and it can interact with endogenous RNAs. We determined the genotype distribution of single-nucleotide polymorphisms (SNPs) within the TLR3 and TLR7 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 59 publications
(76 reference statements)
0
27
0
2
Order By: Relevance
“…TLR3 gene has 6 exons and is located on chromosome 4q35.1 in humans. L412F polymorphism in the TLR3 gene may serve as a genetic risk factor for human cytomegalovirus (HCMV) infection in children [408]. In addition, variant TLR3 genotype rs5743312 (C9948T, intron 3, C > T) is also shown to be significantly associated with increased cancer risk [409].…”
Section: Tlr Polymorphism In Humans and Their Disease Associationmentioning
confidence: 99%
“…TLR3 gene has 6 exons and is located on chromosome 4q35.1 in humans. L412F polymorphism in the TLR3 gene may serve as a genetic risk factor for human cytomegalovirus (HCMV) infection in children [408]. In addition, variant TLR3 genotype rs5743312 (C9948T, intron 3, C > T) is also shown to be significantly associated with increased cancer risk [409].…”
Section: Tlr Polymorphism In Humans and Their Disease Associationmentioning
confidence: 99%
“…In relation to potential variables within the host, genetic polymorphism within our genome would certainly be predicted to impact on an individual's ability to either prevent primary infection or control established persistent infection. Indeed, a wide range of genetic analyses are starting to reveal important associations between genotype and both the risk of primary infection and clinical outcome (35)(36)(37)(38)(39)(40)(41)(42)(43)(44). This important consideration is likely to become even more apparent during the interrogation of very rich epidemiological cohorts that are now available.…”
Section: Why Is the Epidemiology Of CMV Infection In Older People Somentioning
confidence: 99%
“…At least 10 NS SNPs (T50C, A203T, A274C, A293G, T999G, G1197C, G1538A, C1781T, C2108T and A2299T) were shared between chicken breeds in this study and Chi- nese breeds (Huang et al, 2012). Various studies have reported the relationship between polymorphisms in the TLR3 gene and resistance or susceptibility to different viral diseases in human beings (Kindberg et al, 2011;Sironi et al, 2012;Svensson et al, 2012;Lee et al, 2013;Studzińska et al, 2017). Similar relationships between polymorphisms in the TLR3 gene and resistance or susceptibility to various diseases could exist in chickens as well.…”
Section: Tlr3mentioning
confidence: 51%